Analisis Efisiensi, Efektifitas dan Kontribusi Pajak Daerah dan Retribusi Daerah pada Pendapatan Asli Daerah: (Studi Kasus pada Badan Pendapatan Daerah Kabupaten Kupang) - Lidya Even Jelistsa Dima; Yohanes Demu; Maria P. L. Muga (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to determine the efficiency ratio, effectiveness ratio, and contribution ratio of regional taxes and regional levies on the Original Regional Income (PAD) of the Regional Revenue Agency (BAPENDA) of Kupang Regency for the period 2019–2023. This research employs a quantitative descriptive analysis approach using time series data, which are secondary in nature, obtained from relevant official sources. The efficiency ratio measures the extent to which revenue collection processes utilize resources optimally. The effectiveness ratio evaluates the achievement of revenue targets, while the contribution ratio assesses the share of each revenue component toward overall PAD. The findings reveal that the average efficiency ratio of regional taxes and levies in Kupang Regency is 2.00%, which falls under the very efficient criteria. This indicates that the operational costs incurred for collecting these revenues are significantly lower compared to the actual revenue collected, reflecting effective cost management and operational control. The average effectiveness ratio for regional taxes is 82.75%, which is categorized as quite effective, suggesting that most of the revenue targets were achieved during the observation period. In contrast, the effectiveness ratio for regional levies is 34.20%, classified as ineffective, indicating considerable underperformance in meeting revenue targets for levies. Furthermore, the analysis of the contribution ratio shows that regional taxes contribute an average of 99.85% to PAD, which is considered very good and highlights their dominant role as the primary revenue source for Kupang Regency. Conversely, regional levies contribute only 0.69% on average, which falls under the very poor category, suggesting minimal significance in the overall PAD structure. These results emphasize the importance of maintaining the efficiency of tax collection processes while formulating strategies to improve levy collection performance.